The neuropsychological deficits and dissociations in Huntington Disease-Like 2: A series of case-control studies. (January 2020) - Ferreira-Correia, Aline; Anderson, David G.; Cockcroft, Kate; Krause, Amanda
Abstract: Objectives: Huntington's Disease Like-2 (HDL2) is a rare autosomal dominant genetic disease caused by a mutation in the JPH3 gene. The Huntington's Disease (HD) phenocopy has the greatest clinical resemblance to HD, but its neurocognitive characterisation is poorly researched. This study reports on the neurocognitive profile of seven HDL2 patients including preserved functions, deficits and dissociations (classical and strong) and provides a general characterisation of the cognitive dysfunction of HDL2 in relation to the progression of the disease. Methods: The neuropsychological performance of seven HDL2 patients were compared to one of four control groups, matched by age and level of education using a Single Case-Control design. All patients were polyglots and with public education (primary and secondary). Deficits, as well as classical and strong dissociations within each case profile, were identified by implementing Crawford and Howell's (1998) t- test and the Revised Standardized Difference Test (Crawford and Garthwaite, 2005), respectively. Results: The HDL2 neurocognitive syndrome is heterogeneous with a variable rate of progression, with the psychomotor and dexterity domain consistently and severely impaired. Conclusion: HDL2 has a heterogeneous impact on cognitive functions from early stages in the disease, which evolve to dementia in a non-uniform manner, in keeping with preferential damage in the cerebrocortical-basal ganglia-thalamus-cerebrocortical circuit. Highlights: The neuropsychological impairments in HDL2 have an early onset and a heterogeneous progression to dementia. Psychomotor speed and dexterity are the most frequently and severely affected functions in HDL2, followed by visuo-constructive ability. Deficits in executive functions, attention and concentration, and memory and learning are common but heterogeneous. Working memory seems to be unaffected until middle to late stages of the disease progression.